2019
DOI: 10.1016/j.aott.2019.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Reverse shoulder arthroplasty for fracture sequelae: How the initial fracture treatment influences the outcomes of joint replacement

Abstract: ObjectiveThe aim of this study was to analyze and compare the results of reverse shoulder arthroplasty (RSA) in proximal humeral fracture sequelae (PHFS) in fractures initially treated conservatively versus those initially treated with open reduction and internal fixation (ORIF).MethodsIt is a retrospective study that includes all PHFS treated with a RSA from September 2006 to December 2013. Twenty-seven patients met the inclusion criteria. There were 9 patients (7 females and 2 males; mean age: 79.11 years) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
0
7
0
1
Order By: Relevance
“…Previous fracture fixation is also a prejudicial factor with higher rates of complications and revision. 10,37 The fact that GT osteotomy or excision is a prejudicial prognostic factor in patients undergoing RSA for PHFS, with lower functional and subjective results, is not surprising. This has already been shown in studies of RSA for acute proximal humeral fractures 31 and ASA for fracture sequelae.…”
Section: Discussionmentioning
confidence: 99%
“…Previous fracture fixation is also a prejudicial factor with higher rates of complications and revision. 10,37 The fact that GT osteotomy or excision is a prejudicial prognostic factor in patients undergoing RSA for PHFS, with lower functional and subjective results, is not surprising. This has already been shown in studies of RSA for acute proximal humeral fractures 31 and ASA for fracture sequelae.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent studies have noted that patients undergoing salvage RTSA for failed non-operative management may have better outcomes when compared to those undergoing RTSA for failed HA of PHFs. 47 , 48 These findings would suggest that patients at high risk of failing HA may fare better with non-operative management initially with the option to undergo RTSA in the future, if indicated. While this review found statistical significance favoring primary RTSA compared to RTSA as a salvage procedure, the clinical significance of these results is less clear.…”
Section: Discussionmentioning
confidence: 99%
“…[48][49][50][51][52] But in comparing these 2 groups, those undergoing revision for sequelae after initial conservative management show improved functional outcomes. 53,54 In a recent retrospective study conducted by Santana et al, 53 the outcomes for 27 patients were compared after RSA for treatment of fracture sequelae after initial conservative management and RSA for treatment of fracture sequelae after initial management with ORIF. Both groups demonstrated significantly increased Constant scores postoperatively after revision RSA, but patients initially managed conservatively had significantly better outcomes compared with those developing fracture sequelae after initial ORIF management.…”
Section: Primary Versus Secondary Reverse Shoulder Arthroplastymentioning
confidence: 99%